Strategic Management of Digital Literacy Initiatives in Islamic Boarding Schools of Tasikmalaya - Saepurohman, Aep; Badrudin, Badrudin; Erihadiana, Mohamad; Sri Lestari, Ambar; Alai, Ashimatul (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2025)
The rapid advancement of technology has transformed literacy beyond traditional reading and writing skills, making digital literacy a crucial competency in education. In Indonesia, Islamic boarding schools (pesantren) play a significant role in shaping students’ academic and ethical development. However, the integration of digital literacy within pesantren remains understudied, despite its potential to enhance students' ability to access, analyze, and utilize digital information responsibly. Understanding how digital literacy is managed in these institutions is essential for ensuring students are equipped for modern educational and professional environments. This study aims to examine the role of digital literacy management in improving student literacy at Darussalam Islamic Boarding School and Riyadlul Ulum wa Da'wah Islamic Boarding School. It evaluates how structured digital literacy programs contribute to students’ cognitive and practical literacy skills. Using a Mixed Methods approach with Sequential Exploratory design, qualitative data was collected through observation and interviews, while quantitative analysis was conducted using Likert scale questionnaires, Pearson correlation, and Cronbach’s Alpha. Regression analysis indicates that digital literacy management significantly influences student literacy, with R Square values of 0.543 and 0.760, respectively. The findings highlight the need for sustainable digital literacy initiatives, emphasizing ethical technology use. Future research should explore broader impacts to refine educational policies in pesantren.